Antioxidant effect of lemon balm (Melissa officinalis) and mate tea (Ilex paraguensys) on quality, lipid peroxidation and DNA oxidation of cryopreserved boar epididymal spermatozoa - Luño, Victoria; Gil, María Lydia; Olaciregui, Maite; Jerez, Rodrigo A.; De Blas, José Ignacio; Hozbor, Federico Andres (Wiley, 2019)
In this study, we investigated the protective ability of the addition of two antioxidant herb extracts, mate tea and lemon balm, on boar epididymal frozen–thawed spermatozoa quality. Testes from mature boars were collected at local slaughterhouse, and sperm samples from epididymis were recovered by flushing. Spermatozoa were cryopreserved in lactose–egg yolk buffer supplemented with various concentrations of lemon balm and mate tea (0, 2.5, 5 and 10 g l−1) using the straw‐freezing procedure. Motion parameters, acrosome and plasma membrane integrity, lipoperoxidation levels and DNA oxidative damage (8‐hydroxy‐2′‐deoxyguanosine base lesion) were evaluated. There were no differences among experimental groups with regard to motility characteristics, viability, acrosome and plasma membrane integrity; however, the highest concentration of lemon balm produced significant (P < 0.05) improvement in curvilinear trajectory, straightness and amplitude of lateral head displacement after thawing. The supplementation of freezing extender with mate tea and lemon balm reduced sperm lipid membrane peroxidation, and only mate tea protected DNA against oxidative damage during cryopreservation at 120 min post‐thawing (P < 0.05). Mate tea experimental extender at concentration of 10 g l−1 showed the lowest percentage of sperm oxidised DNA and malondialdehyde generation; thus, mate tea is a potential candidate such as antioxidant compound on boar sperm cryopreservation medium.